2009
DOI: 10.1051/0004-6361/200811313
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic survey of the youngest field stars in the solar neighbourhood

Abstract: Aims. We present the first results of an ambitious ground-based observation programme conducted on 1-4 meter class telescopes. Our sample consists of 1097 active and presumably young stars, all of them being optical (Tycho Catalogue) counterparts of ROSAT All-Sky Survey X-ray sources in the northern hemisphere. In this paper, we concentrate on the optically brightest (V T 9. m 5) candidates (704 objects). We acquired high-resolution optical spectroscopy in the Hα and/or lithium spectral regions for 426 of such… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 83 publications
5
75
2
Order By: Relevance
“…Only the UMa stream is clearly separated from the others in the (U, V) plane. It is not unusual that one source may be reported as a candidate of several groups of comoving stars (see, Guillout et al 2009Guillout et al , 2010. In such cases, the stellar properties (and a coherent sky position for the candidate to MGs) help recognize the best SKG match.…”
Section: Testing the Robustness Of Our Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only the UMa stream is clearly separated from the others in the (U, V) plane. It is not unusual that one source may be reported as a candidate of several groups of comoving stars (see, Guillout et al 2009Guillout et al , 2010. In such cases, the stellar properties (and a coherent sky position for the candidate to MGs) help recognize the best SKG match.…”
Section: Testing the Robustness Of Our Methodsmentioning
confidence: 99%
“…Moreover, this SKG is undoubtedly a more complex structure because several nearby young associations have the same kinematics (Zuckerman & Song 2004;Torres et al 2008). As an example, Guillout et al (2009) found that BD+44 3670 is a highly probable candidate of the Pleiades group, while Zuckerman et al (2011) proposed it as a Columba association member. A thorough study of the membership for all the Pleiades MG candidates of these young associations is out of the scope of the present paper and will be addressed in a future work.…”
Section: Kinematic Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Strassmeier et al (2000) presented measurements of equivalent widths of Ca ii H & K, Hα, and Li i in addition to the kinematics of a substantial sample of active and inactive FGK stars. Also, Torres et al (2006) and Guillout et al (2009) determined kinematics and age indicators in comprehensive samples of late-type stars to select members of young moving groups and associations. White et al (2007) determined the same parameters for stars in the Spitzer Legacy Science Program "The Formation and Evolution of Planetary Systems", aimed at studying the formation and evolution of protoplanetary disks.…”
Section: Introductionmentioning
confidence: 99%
“…Only very few spatially unresolved SDSS sources matching 2XMMi entries have combined u − g, g − r and r − i colours compatible with those expected from giant class III stars, not to mention supergiants. In a recent paper, Guillout et al (2009) estimate that their sample of |b| < ∼ 30 • RASS sources identified with bright Tycho stars has a mean contamination of 35% by evolved stars with a peak at 60% for K stars. However, a smaller fraction of X-ray emitting evolved stars of ∼10% was present in the sample of Covey et al (2008), which is more representative of what we should expect in our case because it was selected at higher galactic latitude and fainter flux.…”
Section: X-ray Active Starsmentioning
confidence: 99%